WLAN-GPRS Tight Coupling Based Interworking Architecture with Vertical Handoff Support - Phiri, Fredson Alfred; Murthy, M. B. R. (SPRINGER, 2007)
There have been parallel technological developments in wireless local network (WLAN) and cellular wide area network (WAN) technologies. This is evidenced by the boom in fast WLANs enabled devices, the spread of 2.5 G networks and the increasing emergence 3 G communication networks, applications and terminals. The prospects of integrating WLAN and cellular WAN technologies with support for seamless handoffs between the two heterogeneous have changed the mentality of researchers from considering WLAN technology as a threat to the future of wide area cellular networks to accepting the technology as a complementary solution. A number of architectures for interworking the two different network types have been proposed mainly based on the loose coupling interworking approach recommended by the ETSI. One of the main weaknesses anticipated with loose coupling architecture is excessive handoff latency, which may lead to data loss, traffic congestion and handoff failure. In this paper an architecture for interworking WLAN and the GPRS networks, based on the ETSI tight coupling approach, is proposed.